A combinatorial approach in predicting the outcome of tennis matches - Šarčević, Ana; Vranić, Mihaela; Pintar, Damir (Zielona Góra: Uniwersytet Zielonogórski)
Tennis, as one of the most popular individual sports in the world, holds an important role in the betting world. There are two main categories of bets: pre-match betting, which is conducted before the match starts, and live betting, which allows placing bets during the sporting event. Betting systems rely on setting sports odds, something historically done by domain experts. Setting odds for live betting represents a challenge due to the need to follow events in real-time and react accordingly.
Keywords: binomial distribution; final score prediction; independent and identical distribution; predictive model